Evaluation of urinary trace element levels in patients with opioid use disorder undergoing methadone treatment in western Iran - Nakhaee, Samaneh; Zadeh, Alireza Amirabadi; Madadjoo, Yazdan; Azadi, Nammam Ali; Mansouri, Borhan (Scientific reports, 2024)
The monitoring of essential and toxic elements in patients with Opioid Use Disorder (OUD) undergoing methadone treatment (MT) is important, and there is limited previous research on the urinary levels of these elements in MT patients. Therefore, the present study aimed to analyze certain elements in the context of methadone treatment compared to a healthy group. In this study, patients with opioid use disorder undergoing MT (n = 67) were compared with a healthy group of companions (n = 62) in terms of urinary concentrations of some essential elements (selenium (Se), zinc (Zn), copper (Cu), iron (Fe), manganese (Mn), calcium (Ca)) and toxic elements (lead (Pb), cadmium (Cd), arsenic (As), and chromium (Cr)). Urine samples were prepared using the acid digestion method with a mixture of nitric acid and perchloric acid and assessed using the ICP-MS method. Our results showed that the two groups had no significant differences in terms of gender, education level, occupation, and smoking status. Urinary concentrations of Se, Cu, and Fe levels were significantly lower in the MT group compared to the healthy subjects. However, the concentrations of Pb, Cd, As, Mn, Cr, and Ca in the MT group were higher than in the healthy group ( p < 0.05). No significant difference was established between the levels of Zn in the two groups (p = 0.232). The results of regression analysis revealed that the differences between the concentration levels of all metals (except Zn) between two groups were still remained significant after adjusting for all variables ( p < 0.05). The data obtained in the current study showed lower urinary concentrations of some essential elements and higher levels of some toxic elements in the MT group compared to the healthy subjects. These findings should be incorporated into harm-reduction interventions.